Hyptolide induces ER stress-mediated cell death and enhances GSK3β-regulated cisplatin chemosensitivity in ovarian cancer - Yusi Luluk Rahmania; Person Pesona Renta; Damar Nurwahyu Bima; Yu-Shan Lin; Ngoc Thang Nguyen; Pin-Yu Wang; Meiny Suzery; Wen-Tai Chiu (Journal of Ovarian Research)
Abstract Background Ovarian cancer is a highly prevalent cancer among women with a high risk for relapse and drug resistance. Seventy eight percent of women diagnosed with ovarian cancer live for at least one year after diagnosis. Hyptolide, a natural compound, has been shown to act as an anti-inflammatory and antibacterial agent, and latest research shows that it acts as an anticancer agent. These properties indicate that hyptolide may be a potential treatment option for ovarian cancer, including chemoresistant cases; however, its effects in chemoresistant ovarian cancer have not yet been demonstrated, and the mechanisms underlying its induction of cell death remain unclear. Results We found that hyptolide inhibited cell viability in ovarian cancer cell lines, regardless of their chemoresistance, and these effects were mediated by ER stress and the activation of GRP78 and ATF6. Combined treatment of cisplatin-resistant cell lines with hyptolide and cisplatin demonstrated a synergistic effect, enhancing apoptosis. Additionally, the reversal of chemoresistance with hyptolide treatment was mediated by β-catenin cytoplasm translocation leading to E-cadherin expression, ultimately promoting mesenchymal-epithelial transition. Conclusion Our findings suggest that hyptolide induces ER stress-mediated cell death and overcomes cisplatin chemoresistance in ovarian cancer cells, supporting its potential use as a chemotherapeutic agent.